2016
DOI: 10.3389/fnhum.2016.00480
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Intermittent Theta Burst Stimulation for Suicide Risk in Therapy-Resistant Depressed Patients: A Randomized, Sham-Controlled Trial

Abstract: Objectives: We aimed to examine the effects and safety of accelerated intermittent Theta Burst Stimulation (iTBS) on suicide risk in a group of treatment-resistant unipolar depressed patients, using an extensive suicide assessment scale.Methods: In 50 therapy-resistant, antidepressant-free depressed patients, an intensive protocol of accelerated iTBS was applied over the left dorsolateral prefrontal cortex (DLPFC) in a randomized, sham-controlled crossover design. Patients received 20 iTBS sessions over 4 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 31 publications
6
101
0
1
Order By: Relevance
“…Repetitive TMS of the prefrontal cortex is one therapeutic option for treatment-resistant depression and it is being investigated for use in various mood and cognitive disorders. In order to reduce treatment time, clinics have been exploring the use of short protocols such as TBS (Cash, Dar, et al, 2017a;Desmyter et al, 2016;Duprat et al, 2016;Li et al, 2014), however limited clinical efficacy has also been reported (Prasser et al, 2015). The present data provide the first evidence that using conventional iTBS may not be optimal for neuromo- (Li et al, 2018;Pellicciari, Ponzo, Caltagirone, & Koch, 2017).…”
Section: Inter-individual Variability In the Response To Conventionmentioning
confidence: 76%
See 1 more Smart Citation
“…Repetitive TMS of the prefrontal cortex is one therapeutic option for treatment-resistant depression and it is being investigated for use in various mood and cognitive disorders. In order to reduce treatment time, clinics have been exploring the use of short protocols such as TBS (Cash, Dar, et al, 2017a;Desmyter et al, 2016;Duprat et al, 2016;Li et al, 2014), however limited clinical efficacy has also been reported (Prasser et al, 2015). The present data provide the first evidence that using conventional iTBS may not be optimal for neuromo- (Li et al, 2018;Pellicciari, Ponzo, Caltagirone, & Koch, 2017).…”
Section: Inter-individual Variability In the Response To Conventionmentioning
confidence: 76%
“…In order to reduce treatment time, clinics have been exploring the use of short protocols such as TBS (Cash, Dar, et al, 2017a;Desmyter et al, 2016;Duprat et al, 2016;Li et al, 2014), however limited clinical efficacy has also been reported (Prasser et al, 2015). In order to reduce treatment time, clinics have been exploring the use of short protocols such as TBS (Cash, Dar, et al, 2017a;Desmyter et al, 2016;Duprat et al, 2016;Li et al, 2014), however limited clinical efficacy has also been reported (Prasser et al, 2015).…”
Section: Inter-individual Variability In the Response To Conventionmentioning
confidence: 99%
“…Due to the rapid induction of modulatory effects compared to conventional rTMS, TBS is an attractive option for neuromodulatory treatments in clinical disorders (Chung et al, ; Machado et al, ). For psychiatric conditions, this typically involves stimulation delivered to prefrontal cortical regions such as dorsolateral prefrontal cortex (DLPFC) (Desmyter et al, ; Li et al, ; Plewnia et al, ). As adoption of TBS increases in the clinical literature, the lack of consensus with respect to optimal intensity is becoming increasingly evident.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, TBS in the motor cortex has been applied at 80% of active motor threshold (aMT) (Huang et al, ), equivalent to approximately 70% of resting motor threshold (rMT) (Cardenas‐Morales et al, ; Chen et al, ; Gentner, Wankerl, Reinsberger, Zeller, & Classen, ). Recent reports of the stimulation intensity used in prefrontal TBS for therapeutic intervention have varied quite substantially in the range of 80–120% of rMT (Bakker et al, ; Desmyter et al, ; Duprat et al, ; Li et al, ; Plewnia et al, ; Prasser et al, ). The underlying assumption is that the efficacy of iTBS will be greater with increasing intensity of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Individualized functional connectivity-guided targeting, accelerated delivery and high-dose stimulation were predicted to collectively result in higher response and remission rates than FDA-approved TMS protocols. This protocol was termed 'Stanford Accelerated Intelligent Neuromodulation Therapy (SAINT)' to distinguish this protocol from other attempts at accelerated iTBS delivery without individualized targeting and/or high dose 26,27 . We recently published a smaller series demonstrating efficacy in a cohort with extremely severe and treatment refractory depression 25 .…”
Section: Introductionmentioning
confidence: 99%